ANALISIS IMPLEMENTASI SISTEM TRANSAKSI NON TUNAI DALAM PENGELOLAAN KEUANGAN DAN PENGELOLAAN ASET PADA KELURAHAN TUGU SELATAN DI JAKARTA UTARA - Janah, Baifatul; Ubayanto, Tri; Priyono, Totok (Jurnal Ilmu Administrasi Publik, 2024)
This study describes the implementation of non-cash transaction system in financial management, and asset management in Tugu Selatan village in North Jakarta. This study was motivated by the instruction of the governor of DKI Jakarta Province No. 33 of 2016 concerning the implementation of noncash transactions, with the mandatory non-cash financial transactions within the government of DKI Jakarta. Qualitative research methods with descriptive approach. Data collection technique is done by observation, interview, documentation and triangulation. Research informants determined by purposive sampling. This research was conducted at the South Tugu Village Office. This study aims to analyze the implementation of the system of non-cash transactions in financial management, and asset management, analyze the barriers and efforts made in the settlement of barriers.Based on the results of the study, that the legal basis, flow and procedure of non-cash financial transactions as an instrument has existed as a guide applied to noncash financial transactions. The instrument was disseminated by the transmission process, clarity process, and consistency process as a good communication process to all Tugu Selatan village staff. The competency of the village staff is fulfilled by the implementation of internal training programs, socialization and routine evaluation of the village head and treasurer as the person in charge of the village. Likewise, the need for funds for the implementation of non-cash financial transactions has been provided in the budget when preparing the Performance Plan. Internet network access is available to access the application of Regional Financial Management Information System and CMS Bank DKI. Tugu Selatan village staff are obedient which shows commitment in the implementation of non-cash financial transactions. The flow and procedures of non-cash financial transactions have been implemented by all staff, including staff who deal directly with providing services to the community, with the headman and treasurer in charge. so that it becomes one of the actions of good governance (good governance) in Tugu Selatan village. Factors inhibiting the implementation of non-cash transactions include There are still Tugu Selatan village staff who do not understand all about the flow and procedure of noncash transactions when related to work that requires disbursement of funds, and the internet network slows down when accessing information system applications. The efforts include emphasizing to employees who do not know well about the flow and procedure of non-cash financial transactions, so that they want to learn more about the flow and procedure of non-cash transactions through regular socialization and evaluation, and increasing the bandwidth to 500 Kbps which will increase the speed of internet network access, and the implementation of priority internet